Pelatihan Desain Kemasan Produk Yang Menarik Bagi Pelaku UMKM Kampar - Syaipudin, Muhammad; Reza, Saru; Hidayat, Hidayat (Journal of Community Service and Empowerment, 2024)
Attractive product packaging design training for Micro, Small, and Medium Enterprises (MSMEs) was carried out to increase the competitiveness of local products by improving the quality of packaging. Product packaging functions as a protector and an important marketing tool in building brand image and attracting consumer interest. This training provides knowledge and skills to MSMEs in designing aesthetic, functional packaging that follows product characteristics and target markets. Through a practical approach, the training succeeded in increasing participants' understanding of the importance of packaging in business strategy. The training results showed an increase in the visual quality of the packaging produced by the participants, as well as a positive impact on their product sales. In addition, this training also facilitated the formation of collaborative networks among MSMEs, which can support their sustainable business growth. In conclusion, this training contributed significantly to increasing the competitiveness of MSMEs and is expected to be a model for MSME development programs in the future.